ปัจจัยที่ส่งผลต่อภาพลักษณ์ของศูนย์พัฒนาเด็กก่อนวัยเรียนอิสลาม สังกัดกรุงเทพมหานคร - โต๊ะลง สุธิดา; สิกขาบัณฑิต สุรชัย (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this research were to study: (1) the factors affecting the image of the Islamic Preschool Development Centers; (2) the level of the factors related to the image of the Islamic Preschool Development Centers; and (3) the level of the image of the Islamic Preschool Development Centers. The researcher collected data from a total of 315 people, Data were analyzed by frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The results of the study revealed that: 1) Factors relating to the image of the Islamic Preschool Development Center overall and in each aspect were at a high level. 2) Image of the Islamic Preschool Development Centers overall and all the items of each aspect were at a high level. 3) The results of the study of factors affecting the image of the Islamic Preschool Development Centers were as follows: (3.1) There were relationships between all factors and the image of the Islamic Preschool Development Centers at a .05 level of significance. (3.2) It was found that all 6 factors could be the best image predictors of the Islamic Preschool Development Centers as follows: strategic management, child factor, managerial factor, personnel factor, curriculum and instructional factors, and location building factor.